Agility Strategy and Risk Management as Support for Sustainable MSME Performance to Achieve MSME SDGs: A Literature Review - Ivan Widjaja; Sudarmiatin Sudarmiatin; Ludi Wishnu Wardana (Universitas Veteran Bangun Nusantara Sukoharjo, 2024)
The vital role of SMEs worldwide in generating employment, creating added value, and driving inclusive economic development is widely recognized. However, SMEs often face challenges such as limited access to resources, difficulties in adapting quickly to change, and uncertainties within the business environment. This study aims to explore the integrated application of agility strategies and risk management to enhance SME performance and resilience, ultimately contributing to the achievement of global SDGs. The novelty of this research lies in its comprehensive analysis of the synergy between these two approaches in the context of sustainable SME performance, a topic that has not been extensively explored. The urgency of this study stems from the need to strengthen SMEs so they can maximize their role in achieving SDG goals related to poverty alleviation, job creation, and inclusive economic development worldwide. The method employed in this research is a Systematic Literature Review (SLR), which involves gathering and analyzing relevant journal articles using VOSviewer software in relation to the chosen keywords. The findings indicate that combining agility strategies with risk management improves SMEs' capacity to adapt quickly, seize opportunities, and manage a range of business risks effectively. This research advocates for a holistic approach by integrating agility strategies and risk management to achieve optimal, sustainable performance, thereby supporting sustainable development goals on a global scale.